Neoadjuvant toripalimab combined with axitinib in patients with locally advanced clear cell renal cell carcinoma: a single-arm, phase II trial - Wei Zhang; Ding Zhang; Fan Xu; Wei Xue; Jin Zhang; Xiaorong Wu; Guangyu Wu; Jiwei Huang; Yueming Wang; Zaoyu Wang; Wen Kong; NG Cheoklong; et al. (Journal for ImmunoTherapy of Cancer)
Background A combination of axitinib and immune checkpoint inhibitors (ICIs) demonstrated promising efficacy in the treatment of advanced renal cell carcinoma (RCC). This study aims to prospectively evaluate the safety, efficacy, and biomarkers of neoadjuvant toripalimab plus axitinib in non-metastatic clear cell RCC.Methods This is a single-institution, single-arm phase II clinical trial. Patients with non-metastatic biopsy-proven clear cell RCC (T2-T3N0-1M0) are enrolled. Patients will receive axitinib 5 mg twice daily combined with toripalimab 240 mg every 3 weeks (three cycles) for up to 12 weeks. Patients then will receive partial (PN) or radical nephrectomy (RN) after neoadjuvant therapy. The primary endpoint is objective response rate (ORR). Secondary endpoints include disease-free survival, safety, and perioperative complication rate. Predictive biomarkers are involved in exploratory analysis.Results A total of 20 patients were enrolled in the study, with 19 of them undergoing surgery. One patient declined surgery. The primary endpoint ORR was 45%. The posterior distribution of πORR had a mean of 0.44 (95% credible intervals: 0.24–0.64), meeting the predefined primary endpoint with an ORR of 32%. Tumor shrinkage was observed in 95% of patients prior to nephrectomy. Furthermore, four patients achieved a pathological complete response. Grade ≥3 adverse events occurred in 25% of patients, including hypertension, hyperglycemia, glutamic pyruvic transaminase/glutamic oxaloacetic transaminase (ALT/AST) increase, and proteinuria. Postoperatively, one grade 4a and eight grade 1–2 complications were noted. In comparison to patients with stable disease, responders exhibited significant differences in immune factors such as Arginase 1(ARG1), Melanoma antigen (MAGEs), Dendritic Cell (DC), TNF Superfamily Member 13 (TNFSF13), Apelin Receptor (APLNR), and C-C Motif Chemokine Ligand 3 Like 1 (CCL3-L1). The limitation of this trial was the small sample size.Conclusion Neoadjuvant toripalimab combined with axitinib shows encouraging activity and acceptable toxicity in locally advanced clear cell RCC and warrants further study.Trial registration number clinicaltrials.gov, NCT04118855.